The Effect of Job Division, Promotion, Project, Salary, Length of Work With Employee Turnover Using Logistic Regression Analysis - Sitti Raisya Fitri Effendi (Publikasi Indonesia, 2024)
This study aims to examine the effect of job division, employee promotion, projects, salary, and length of work on employee turnover rates in an organization. The use of logistic regression analysis is used to identify factors that contribute to employees' decision to leave their jobs. Data for this study was collected through surveys involving employees in various divisions within the selected organization. The dependent variable is the employee's turnover status (resigning or not resigning), while the independent variable includes job division, employee promotion, project, salary, and length of work. The results of logistic regression analysis show that Employee Salary has a significant influence on employee turnover rate. A competitive salary can be a determining factor in influencing an employee's decision to stay in the job. The results of this study have a sensitivity level of 45%, meaning the goodness of the model in predicting employees who do not leave the company. The results showed that the level of specificity is 82% predicting employees who leave the company so this model is very good in this case. The results of this study provide important insights for organizational management in managing employee turnover rates. By understanding the influence of these factors, organizations can take appropriate steps to increase employee satisfaction, retain valuable talent, and reduce costs and disruptions caused by employee turnover.